ONE STAGE SURGERY OF CONGENITAL DISLOCATION OF HIP IN CHILDREN OF 2-5 YEARS OF AGE - Shabir, Muhammad; Arif, Muhammad; Inam, Muhammad (Journal of Postgraduate Medical Institute, 2011)
Objective: To evaluate the results of a single stage combined procedure for congenital dislocation of the hip in 2-5 years age group. Material and Methods: This descriptive study was conducted at the Department of Orthopaedic Surgery, Hayatabad Medical Complex, Peshawar, from September 2003 to July 2007. There were 25 patients with 30 hips who were operated for congenital dislocation and who presented after two years of age. The procedure consisted of arthrotomy, femoral shortening, derotational varus osteotomy and capsulorraphy. Pelvic osteotomy done where required. Pre-operative and post-operative clinical and radiological assessment was done according to modified McKay and Severin criteria and patients were followed up for 6 months to one year. Results: There were 17 girls and eight boys in this study. Mean age was 38.56 + 12.43 months. Five cases had bilateral dislocation. Postoperatively, 18 hips operated were rated excellent by using McKay criteria, seven were rated as good and five as fair. Five children had residual pain, limitation of movement of the hip and positive-Trendlenberg post-operatively. The Severin Classification demonstrated 9 hips of grade IA, six of grade IB, ten of grade II and five of grade III. Two patients of grade II had avascular necrosis of head of femur. Conclusion: One stage correction of congenital dislocation of the hip in children of 2-5 years age is a safe and effective treatment with good results in the short to medium term.